Analysing Shortest Route Problem in Petaling Jaya: A Case Study - Ilmi Samsulazlan, Muhammad Shahrul; Mohd Nawawi, Mohd Kamal; Abduljabbar, Waleed Khalid; Sufahani, Suliadi Firdaus (International Journal of Supply Chain Management, 2020)
In graph theory, the shortest path problem is the problem of finding a path between two vertices or nodes in a graph such that the sum of the weights of its constituent edges is minimized. Shortest path is important to minimize total travelling time or cost. This paper presents a current method to construct the solution on shortest route in Petaling Jaya district area for research staff doing a survey tour. Integer linear programming (ILP), heuristic method and Google Maps were used to analyse the travelling salesman problem (TSP). Result shows that it has agreement with theoretical predictions and significant improvement over previous efforts by researchers. The work presented here has profound implications for future studies of saving time and cost behaviour and may help to solve the problem for the survey tour in the future